(untitled) (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2026)
Along with written sources in various languages, archaeological finds also play a special role in shedding light on the relations between Sughd and Ustrushona. In particular, archaeological materials obtained during archaeological excavations conducted for almost a hundred years in the ruins of ancient settlements in the territories of historical Sughd - Zarafshan and Kash-Kadarya oases and Jizzakh and Istaravshan (Uratepa) regions - the topography of cities, numismatic and epigraphic monuments - give a certain idea of the interaction of both regions with each other. At the same time, toponyms - place names and onomastics can also be included among the historical materials that provide important information about the historical relations between Sughd and Ustrushona.